Afterword: They say the Centre cannot hold: Austerity, crisis, and the rise of anti-politics - Drago, Ana (2020)
This afterword engages in a dialogue with the theoretical prospects opened by this Special Issue. First, it discusses how these articles show that conceptualizations such as anti-politics that aimed to organize a reading on the growing mistrust and disenchantment towards the institutional apparatus of contemporary democracies must not be equated to political voidance – I argue that these articles rather point to a profound legitimization crisis of the political-spatial consensus of neoliberal governance that, as this SI sustains, must be analyzed through the social and geographical configurations of the austerity cycle of the last decade and the situated conflict confronting it. In that sense, anti-politics redefines traditional conflict in liberal democracies, although through contradictory forms: commoning; radical protest; or ethno-nationalist extremism. And secondly, I discuss a most relevant argument that runs through the SI: analysis of anti-politics must engage with everyday spatial practices and geographical imaginaries that point where conflict arises, but also how it is being recrafted. I discuss this proposal of a spatial turn on anti-politics by interpreting it as emerging from the collapse of the aspirational narrative of neoliberalism– its promise of a global post-class conflict order succumbed as post-2008 austerity punitively targeted specific geographies, spaces and social classes, leading to a cycle of politicization organized through spatial or geographical dichotomies: North/South Europe; urban versus periurban/rural; streets versus institutions. After decades of neoliberal depoliticization of class conflict, attempts to relaunch anti-systemic political conflict seem to rely (again) on everyday spatial practices and geographical categories.